Our Angry Eden Faith and Hope on a Hotter, Harsher Planet. - Williams, David (Broadleaf Books, 2021)
The planet we will pass on is different than the one we inherited. Living with our angry Eden will involve a period of sustained difficulty and disruption. David Williams, author of When the English Fall, spells out how we will be morally tested, outlines nine virtues key to human thriving in the decades to come, and beckons readers toward a faith and a hope resilient enough to face the effects of the climate crisis.